TRADISI MANDI SAFAR DI KELURAHAN TELUK PINANG KECAMATAN GAUNG ANAK SERKA KABUPATEN INDRAGIRI HILIR - Krisna Ayu Piya Utari; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research is titled The Tradition of Safar Bathing in Teluk Pinang village, Gaung Anak Serka District, Indragiri Hilir Regency. Based on the history of the Safar Bathing Tradition in Teluk Pinang Village, it has been done for a long time since Teluk Pinang was first opened. The safar bathing which was done by the community of Teluk Pinang village was initially to keep danger away, because when the Teluk Pinang village was just opened, there was a lot of poison, disease and reinforcements. By the village opening initiative, a safar bath was held to ask Allah SWT for protection to avoid things that are not desirable. This study aims to describe the process of implementing the Mandi Safar Tradition, and to find out why the community of Teluk Pinang Village still maintains the tradition up to now. Researchers used a purposive sampling technique that included community leaders, religious leaders, village guards, confidants from village guards and the community of Teluk Pinang Kelurahan. To analyze the research data descriptive qualitative data collected then presented descriptively that is describing or telling the results of research with a description of logical sentences so that they can be understood and easily understood. This research was conducted in Teluk Pinang village, Gaung Anak Serka District, Indragiri Hilir Regency. The results of the research show that the Survival of the Safar Bathing Tradition is that it cannot be left out or lost. Even though today is modern, the existing traditions must be maintained and maintained. This safar bath is certainly a form of endeavor of the local community, to be protected by Allah SWT from bad things that can be seen from the writing of words taken from fragments of the Qur'an. Keywords: Process, Safar Bath, Tradition.